International management strategic opportunities and cultural challenges - McFarlin, Dean B; Sweeney, Paul D (Routledge, 2015)
Offers an application-oriented approach to international management, focusing on key challenges including motivation, leadership, and communication across cultural boundaries. This book provides a global perspective on the process of hiring, training, and developing employees, as well as strategic decision making in relation to foreign markets